ELEVATE-LNP: Empty lipid nanoparticle enabled validation and AI-guided therapeutic evaluation for efficient formulation optimization for mRNA delivery - Mingzhi Yu; Luhan Wang; Timothy Elliott; Xianqing Wang; Allen Mathew; Bei Qiu; Liang Yao; Wenxin Wang; Nan Zhang (Chemical Engineering Journal, 2026)

Use of translational fusions to express functional Klebsiella oxytoca dinitrogenase reductase in plant mitochondria - Shoko Okada; Xueqin Wang; Christina M. Gregg; Robert S. Allen; Timothy Rhodes; Vanessa Gillespie; Ingrid Venables; Anu Mathew; Jessica K. Bilyj; Keren Byrne; Robert C. DeFeyter; Trevor D. Rapson; et al. (Plant Molecular Biology, 2026)
Engineering crop plants with the biological nitrogen fixation pathway is a longstanding goal of modern agriculture. Dinitrogenase reductase (NifH) is a critical component of the biological nitrogen fixation pathway, with multiple roles in metal cofactor assembly and catalysis. This enzyme must be folded correctly as a soluble homodimer and loaded with the [4Fe-4S] metallocluster for function. Previous studies have found that Klebsiella oxytoca ( Ko ) and Azotobacter vinelandii ( Av ) NifHs were mostly insoluble when targeted to plant mitochondria. Here we found that a translational fusion of two Ko NifH or Av NifH monomers, forming Ko NifHH or Av NifHH synthetic dimers, produced a soluble protein when targeted to plant mitochondria and co-expressed with the putative peptidyl-prolyl cis–trans isomerase NifM. Ko NifHH isolated after expression in leaf mitochondria at ambient oxygen showed some acetylene reduction activity, which did not require co-expression of the nitrogenase-specific metallocluster machinery NifS and NifU. This activity increased after iron-sulfur cluster reconstitution in vitro with recombinant NifU. In a parallel study, we tested a translational fusion of a variant iron-only dinitrogenase reductase ( Av AnfHv6) monomer that was soluble but not active as-isolated from plant mitochondria ( Av AnfHHv6) (Gregg et al. 2025a). Av AnfHHv6 was abundant and fully soluble when isolated from plant mitochondria, like its monomer. Av AnfHHv6 was not active as-isolated but could be largely activated by iron-sulfur cluster reconstitution in vitro. This study demonstrates how translational fusions help improve solubility and have the potential to generate an active NifH enzyme within plant mitochondria.

Motivations and barriers to integrated management of annual bluegrass in sports fields: US survey findings - David E. Ervin; George B. Frisvold; Jennifer H. Allen; Aaron J. Patton; James T. Brosnan; Rebecca Grubbs Bowling; Mathew T. Elmore; Muthukumar V. Bagavathiannan; James D. McCurdy; Travis W. Gannon; John E. Kaminski; Alec R. Kowaleski; et al. (Urban Forestry & Urban Greening, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

SNTG1, the gene encoding ?1-syntrophin: a candidate gene for idiopathic scoliosis - Stavros Bashiardes; Rose Veile; Missy Allen; Carol A. Wise; Mathew Dobbs; Jose A. Morcuende; Lazlos Szappanos; John A. Herring; Anne M. Bowcock; Michael Lovett (Human Genetics, 2004)

Control of Ixodes scapularis and Amblyomma americanum Through use of the ‘4-poster’ Treatment Device on Deer in Maryland - John F. Carroll; Patricia C. Allen; Dolores E. Hill; J. Mathews Pound; J. Allen Miller; John E. George (Experimental and Applied Acarology, 2002)